Analisis Penerapan Total Quality Management dengan Pendekatan Process Centered pada Kualitas Produksi Dapur MBG - Raditya Anugrah Sarbini; Resi Juariah Susanto (PT. Hasba Edukasi Mandiri, 2026)
This study analyzes the implementation of Total Quality Management (TQM) with a process-centered approach to improve production quality at the Makan Bergizi Gratis (MBG) kitchen on Jalan Soekarno Hatta No. 199, Babakan Ciparay, Bandung. Using a descriptive qualitative approach, data were collected through observations, interviews, documentation, and a satisfaction questionnaire involving 100 student beneficiaries from six schools. Production quality was evaluated using five indicators: Process Capability Index (Cp/Cpk), Overall Equipment Effectiveness (OEE), First Pass Yield (FPY), Food Waste Rate, and Customer Satisfaction Index (CSI). The results show that OEE (87.40%) and FPY (98.26%) exceeded the research targets, while Cpk (0.78), Food Waste Rate (6.40%), and CSI (86.92%) remained below the expected values. Overall, the process-centered approach improved operational effectiveness and production quality, although process consistency, raw-material efficiency, and beneficiary satisfaction still require continuous improvement.